Functional ability and health status of community-dwelling late age elderly people with and without a history of falls - Thiwabhorn Thaweewannakij, PT, PhD; Patcharawan Suwannarat, PT, PhD candidate; Lugkana Mato, PT, PhD; Sugalya Amatachaya, PT, PhD (World Scientific Publishing, 2016)
Background: Obvious functional deterioration is demonstrated in elderly people aged 75 years and older. However, there is only little objective evidence relating to falls in these individuals. Objective: This cross-sectional study compared functional abilities and health status in the elderly age at least 75 years with no fall, single fall (1 fall), and multiple falls (≥2 falls) during the past 6 months. Furthermore, the study describes fall information of the participants. Methods: Ninety participants (30 individuals/group) were interviewed for their health status and fall history within the past 6 months. Then they were objectively assessed in terms of their functional ability to conduct daily activities independently. Results: The findings indicated that the functional abilities of participants with multiple falls were significantly poorer, with the number of those requiring a walking device significantly greater than that in the other groups. These individuals reported loss of balance as a major factor for falls, whereas individuals with a single fall reported an environmental hazard as a common cause of falls. Conclusion: Although the cross-sectional findings may be unable to clearly confirm the causal relationship of the outcomes, the data support the influence of intrinsic impairments and can be used to promote functional ability and minimise fall risk in these individuals.